2020
DOI: 10.2147/ppa.s260404
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of a Patient-Centered Weight Management Model in a Community Pharmacy: An Interventional Study</p>

Abstract: The aim of this study was to evaluate the provision of a professional pharmaceutical patient-centered model in a weight management program and optimization of the medication in a Spanish community pharmacy. Patients and Methods: This was a single-group intervention study with a mean follow-up period of 8.2 months (sd 2.3). Patients ≥18 years old seeking to lose weight or improve eating habits were recruited. On the first visit, the pharmacist collected patients' sociodemographic and anthropometric variables, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…PCC has been associated with improved patient outcomes in various healthcare settings, 26 including the provision of care to patients with obesity 27 . However, the relative importance of the different aspects of PCC seems to vary among patient groups 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC has been associated with improved patient outcomes in various healthcare settings, 26 including the provision of care to patients with obesity 27 . However, the relative importance of the different aspects of PCC seems to vary among patient groups 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…PCC has been associated with improved patient outcomes in various healthcare settings, 26 including the provision of care to patients with obesity. 27 However, the relative importance of the different aspects of PCC seems to vary among patient groups. 28 , 29 Although aspects of care that may be important specifically for patients with obesity have been identified, the significance of the eight dimensions of PCC for patients with obesity has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…observed that the patient-oriented weight management approach had a positive effect on the improvement of all clinical and therapeutic outcomes in research to ascertain its effects in community pharmacies [9].…”
Section: Introductionmentioning
confidence: 99%